Literature Review: Methods for Prevention And Control Of Pulmonary Complications In Active Cycle Breathing - Peluw, Zulfikar; Ningsih, Eka Sarofah; Ruben, Sethiana Dewi; Aryadi, Anggi; Tandiola, Rosdiana; Rahagia, Rasi; Minarti, Minarti (International Journal of Health Sciences, 2024)
The decrease in lung functional capacity will be followed by a decrease in the value of maximal inspiratory pressure and maximal expiratory pressure, both of these values indicate a significant decrease in respiratory muscle strength after the Coronary Artery Bypass Graft procedure, which can increase mortality rates and length of hospital stay. The purpose of this study was to repair blocked and narrowed arteries by cutting and replacing the blocked arteries from healthy vessels. The research method used the Patient method: Post ACBG; intervention: active cycle of breathing technique; comparison: other physiotherapy interventions; outcome: functional lung capacity. The results showed that active cycle of breathing technique and routine chest physiotherapy interventions had the same effect on reducing pain, this was evidenced by a p-value of 0.001 which means that active cycle of breathing technique and routine chest physiotherapy showed a significant effect on reducing pain in post coronary artery bypass graft patients. The conclusion of this study is that Active Cycle of Breathing Technique exercises have been proven to improve the functional lung capacity of post coronary artery bypass graft patients.